STRATEGI PENERAPAN DOMAIN AFEKTIF DI LINGKUP PERGURUAN TINGGI - Wicaksono, Soetam Rizky (LPPM Universitas Terbuka, 2011)
The application of affectiveeducation forcollegestudent cannotbe explicitlydone bylecturers or parents alone, butneeds aspecial strategyin order to havea significant impact on their character development. Based on experience in the relevant fields, the impact of affectiveeducationis oftenoverlookedby teachersand researchersbecause they thoughtthe affectivedomainis verydifficult to measureandhighlydependentonotherfactors. This paperpresents someimplementationstrategiesbased on theaffectivedomain ofliterature reviewtofind astrategy to implementthe affectivedomainforcollegestudent groups. The results ofthis studyis expected tobe afoundation forfutureempiricalresearch.